2008
DOI: 10.1159/000131669
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Incidence in Women under 60 Years of Age Related to Alcohol Intake and Smoking Habit

Abstract: Background and Purpose: The association between alcohol intake, cigarette smoking and risk of stroke amongst women remains unclear, especially in young women. Methods: This prospective cohort study included 45,449 Swedish women aged 30–50 years free of stroke and heart diseases at enrolment in 1991 and 1992. Information on drinking and smoking habits at enrolment was collected using a questionnaire. Incident stroke cases were identified through cross-linkage to the Swedish Inpatient Register. Cox proportional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 90 publications
2
29
0
Order By: Relevance
“…Because of its large size and prolonged follow-up, the number of stroke cases involved in the study was larger compared with earlier cohort studies. Previous analyses from this cohort confirmed the increased risk of ischemic stroke among women who smoked, 22 and those with lower educational levels, 13 indicating that there was sufficient power to identify real effects. Moreover, the women in the cohort were likely to be representative of the general population in terms of risk factor profiles, making the results more generalizable.…”
Section: Discussionsupporting
confidence: 54%
“…Because of its large size and prolonged follow-up, the number of stroke cases involved in the study was larger compared with earlier cohort studies. Previous analyses from this cohort confirmed the increased risk of ischemic stroke among women who smoked, 22 and those with lower educational levels, 13 indicating that there was sufficient power to identify real effects. Moreover, the women in the cohort were likely to be representative of the general population in terms of risk factor profiles, making the results more generalizable.…”
Section: Discussionsupporting
confidence: 54%
“…245 Smoking increases the RR of ischemic stroke by 25% to 50%. [247][248][249][250][251][252][253] Stroke risk decreases substantially within 5 years in those who quit smoking compared with continuing smokers. 248,250 In large epidemiological studies, cigarette smoking has been associated with extracranial carotid artery IMT and the severity of carotid artery stenosis.…”
Section: Medical Therapy For Patients With Atherosclerotic Disease Ofmentioning
confidence: 99%
“…A recent pooled cohort of the Atherosclerosis Risk In Community study and Cardiovascular Health Study of 15 792 US adults did not find any consistent or independent relationship of smoking with ICH incidence or deaths. 22 However, this and other such studies [21][22][23] might also be underpowered because of low hemorrhagic stroke incidence, although most of these studies found indications of a harmful effect.…”
Section: August 2013mentioning
confidence: 89%
“…[21][22][23] A nested case-control study in Sweden, including 147 ICH cases and 1029 controls, reported that smoking was not a risk factor for primary ICH 21 incidence or deaths. Another study of ≈45 000 Swedish women also found no statistically significant association of smoking with ICH incidence or deaths 23 ; although the risk for ICH was higher in women who smoked 1 to 9 cigarettes per day (HR=1.5), the small number of ICH cases (n=15) did not provide sufficient statistical power for a more reliable conclusion. A recent pooled cohort of the Atherosclerosis Risk In Community study and Cardiovascular Health Study of 15 792 US adults did not find any consistent or independent relationship of smoking with ICH incidence or deaths.…”
Section: August 2013mentioning
confidence: 99%